Analisis Perbandingan Rab Penggunaan Bata Merah Dan Bata Ringan (Hebel) Pada Rumah Tinggal Sederhana Tipe 36 (Studi Kasus Kota Palopo) - Noviana Noviana; Anggel Erpa Erong Pakiding (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Resource management and the selection of appropriate wall materials in the construction of simple type 36 residential houses play a crucial role in achieving cost efficiency without compromising building quality and structural standards. Wall masonry is one of the non-structural components with the largest work volume, absorbing a significant portion of the total budget. This study aims to analyze and compare the Budget Plan (RAB) and cost efficiency between conventional red brick and modern lightweight aerated concrete brick (Hebel) in the construction of a simple type 36 residential house in Palopo City, South Sulawesi. The research method applied is descriptive quantitative comparative analysis through field observations and mathematical calculations of net wall volume, Unit Price Analysis of Work (AHSP) based on local standards and material availability, as well as the total cost recapitulation of both materials. Based on the floor plan analysis, a net wall volume of  was obtained (after deducting  for door and window openings). The results of the unit price analysis (AHSP) per  showed that red brick masonry work costs IDR 153,830.00, whereas lightweight brick masonry costs IDR 116,230.00. In terms of total execution cost, wall work using red brick requires a budget of IDR 13,844,700.00, while converting to lightweight brick requires IDR 10,460,700.00. The application of lightweight brick (Hebel) is proven to generate cost savings of IDR 3,384,000.00, which corresponds to a budget efficiency of 24.44%. The primary factors driving the high efficiency of lightweight bricks are the lower labor coefficient due to precise block dimensions, faster installation times, and reduced adhesive material consumption using thin-bed mortar cement ( ). Therefore, lightweight brick (Hebel) is highly recommended as the most economical and optimal wall material choice for property developers and self-build communities in Palopo City.